Evaluation of Local Pediatric Out-of-Hospital Cardiac Arrest and Emergency Services Response - McKenzie, Kate; Cameron, Saoirse; Odoardi, Natalya; Gray, Katelyn; Miller, Michael R.; Tijssen, Janice A. (Frontiers in Pediatrics, 2022)
Background: Survival after paediatric out-of-hospital cardiac arrest is poor. Paramedic services provide critical interventions that impact survival outcomes. We aimed to describe local paediatric out-of-hospital cardiac arrest (POHCA) events and evaluate the impact of the paramedic service response to POHCA. Methods: The Canadian Resuscitation Outcomes Consortium and corresponding ambulance call records were used to evaluate deviations from best practice by paramedics for patients aged 1 day to <18 years who had an atraumatic out-of-hospital cardiac arrest between 2012 and 2020 in Middlesex-London County. Deviations were any departure from protocol as defined by Middlesex-London Paramedic Services. Results: Fifty-one patients were included in this study. All POHCA events had at least one deviation, with a total of 188 deviations for the study cohort. Return of spontaneous circulation (ROSC) was achieved in 35.3% of patients and 5.8% survived to hospital discharge. All survivors developed a new, severe neurological impairment. Medication deviations were most common (n=40, 21.3%) followed by process timing (n=38, 20.2%), vascular access (n=27, 14.4%), and airway (n=27, 14.4%). A delay in vascular access was the most common deviation (n=25, 49.0%). The median (IQR) time to epinephrine administration was 8.6 (5.90-10.95) minutes from paramedic arrival. Cardiac arrests occurring in public settings had more deviations than private settings (p=0.04). ROSC was higher in events with a deviation in any circulation category (p=0.03). Conclusions: Patient and arrest characteristics were similar to other POHCA studies. This cohort exhibited high rates of ROSC and bystander cardiopulmonary resuscitation but low survival to hospital discharge. The study was underpowered for its primary outcome of survival. The total deviations scored was low relative to the total number of tasks in a resuscitation. Epinephrine was frequently administered outside of the recommended timeframe, highlighting an important quality improvement opportunity.